A refined method for estimating the number of earthworm chaetae in carnivore feces. Issue 4 (12th April 2021) - Tsukada, Hideharu; Nishikawa, Yuka; Shimada, Haruka; Hijikata, Koji; Minami, Masato
Abstract: Generally, earthworm chaetae in feces are counted to estimate the contribution of earthworms to carnivore diets. In this study, we compared three methods: (1) a part of the wet fecal sample soaked in alcohol to attain 100% humidity was directly extracted, (2) after removing the extra alcohol from the wet sample maintained at 100% humidity was extracted, and (3) the entire wet fecal sample was homogenized and a random part was extracted to detect the number of earthworm chaetae in fecal samples by focusing on sensitivity, precision, and efficiency. The third method yielded the best results in terms of sensitivity and accuracy in detecting chaetae, but the second highest and moderate results in terms of efficiency and treatment time. This method was used to analyze the fecal samples of Japanese badgers and raccoon dogs. The size of earthworm chaetae recovered from the feces differed significantly between species and seasons, especially in spring, suggesting that the Japanese badgers and raccoon dogs may feed mainly on different earthworm families in spring. Therefore, a refined method was proposed in this study to quantitatively and efficiently detect earthworm chaetae in carnivore feces. Abstract : To estimate the contribution of earthworms to carnivore diets, we refined a method estimating the number of earthworm chaetae in carnivore feces. For that, the entire wet fecal sample was homogenized and a random part was extracted to detect the number of earthworm chaetae. This method was used to analyze the fecal samples of Japanese badgers and raccoon dogs. The size of earthworm chaetae recovered from the feces differed significantly between species and seasons, especially in spring, suggesting that the Japanese badgers and raccoon dogs may feed mainly on different earthworm families in spring.